2015
DOI: 10.1016/j.jallcom.2015.06.084
|View full text |Cite
|
Sign up to set email alerts
|

Structure of 3 at.% and 9 at.% Si-doped HfO2 from combined refinement of X-ray and neutron diffraction patterns

Abstract: a b s t r a c tThe crystal structure of 3 at.% and 9 at.% Si-doped HfO 2 powder was determined through refinements using X-ray and neutron diffraction patterns. The lattice parameters, atomic positions, dopant occupancy, and the second phase fraction were determined with high precision using a combined full pattern fitting via the Rietveld method. The results show that both 3 at.% and 9 at.% Si-doped HfO 2 powder exhibit the monoclinic crystal structure with P 1 2 1 /c 1 space group. Through the combined refin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Here, p is electric dipole moment, ε r is the relative dielectric constant and is set to 25, and r is the distance from the center of electric dipole moment to a fixed point and is set to 4.3 Å, considering the well-known lattice constant of HfO 2 (50 Å). [40,41] N grain is the number of the grains present in the thin film, N molecule is the number of switchable molecules present in the grain, and PDF(t) is the probability density function set to the normal distribution formula that represents the polarization switching in a multi-domain ferroelectric. In the single-domain ferroelectric thin film, when a domain nucleus is formed inside the ferroelectric thin film without the nucleation of an additional domain, it grows horizontally, and eventually changes the polarization direction for the entire domain.…”
Section: T P Rmentioning
confidence: 99%
“…Here, p is electric dipole moment, ε r is the relative dielectric constant and is set to 25, and r is the distance from the center of electric dipole moment to a fixed point and is set to 4.3 Å, considering the well-known lattice constant of HfO 2 (50 Å). [40,41] N grain is the number of the grains present in the thin film, N molecule is the number of switchable molecules present in the grain, and PDF(t) is the probability density function set to the normal distribution formula that represents the polarization switching in a multi-domain ferroelectric. In the single-domain ferroelectric thin film, when a domain nucleus is formed inside the ferroelectric thin film without the nucleation of an additional domain, it grows horizontally, and eventually changes the polarization direction for the entire domain.…”
Section: T P Rmentioning
confidence: 99%
“…Later, Haines et al (1997) performed an ND study on HfO 2 synthesized by quenching the sample from 800 C and 20 GPa, and reported a cotunnite structure. On the other hand, the ND technique has been applied for studying the structure of 3 and 9 at% Si-doped HfO 2 by Zhao et al (2015). The ND method was used along with XRD and molecular dynamics simulations to characterize two structurally disordered forms of hafnia, i.e.…”
Section: Introductionmentioning
confidence: 99%